Identity Politics and Inter-Religious Relations: Analysing the 2020 Election in Manado City - Gerry Nelwan (UIN Sunan Gunung Djati, 2022)
The 2020 Pilkada (pemilihan kepala daerah) in Manado City has had a lot of influence on the dynamics of society, one of which is the presence of religion-based identity politics. Political contestation by utilizing religious identity occurs because religion can become the basis of voice. But its impact on interfaith relations has been lack of attention or neglected. The purpose of this study is to analyze the impact of religion-based identity politics that occurred in the Pilkada of Manado City on the relationship between Christianity and Islam. This research provides another perspective on politics in Manado City in the academic world and practically for the government and related institutions. This study used a descriptive qualitative method with a literature study, in which observations and literature studies were carried out. In this literature study, researchers used a variety of scientific writings, journal articles, books, newspapers and online news that are related to research. When the political battle began, the pilkada participants began to reveal their religious identity in the public sphere. This invites various reaction from the society to see the participants from their religious identity. Relations in society began to be disturbed when political talks were always side by side with religion. So what happens is that people support their candidates because of religion. This situation is considered to disturb inter-religious harmony in Manado City, especially Christianity and Islam.